2020
DOI: 10.1017/rdc.2020.37
|View full text |Cite
|
Sign up to set email alerts
|

Dating Adoption and Intensification of Food-Crops: Insights From 4msr (Binjor), an Indus (Harappan) Site in Northwestern India

Abstract: Here we present direct dates of food grains and insights into agricultural strategies adopted by Harappans from a newly excavated Indus site 4MSR (Binjor) in northwestern India. The site revealed Early and Mature Harappan phases delimited by a Transitional phase based on ceramics and archaeological artifacts. The macro-botanical remains revealed that the site was occupied by an agricultural society during the Early phase (~2900−2600 BCE), whereas diversification of the economy including more craft specializati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 71 publications
(84 reference statements)
1
13
0
Order By: Relevance
“…2000 BCE (Lone et al, 2020;Shah et al, 2020;Spate et al, 2022a), as has been noted elsewhere in Central Asia (Motuzaite Matuzeviciute et al, 2021). Sharma et al (2020), based on a comprehensive account of macro-botanical remains and direct dates of food grains from Binjor, an Indus Valley (Harappan) site in northwestern India, revealed that the area was occupied by an agricultural society during the Early Phase (ca. 2900−2600 BCE).…”
Section: Late Glacial Tomentioning
confidence: 69%
See 1 more Smart Citation
“…2000 BCE (Lone et al, 2020;Shah et al, 2020;Spate et al, 2022a), as has been noted elsewhere in Central Asia (Motuzaite Matuzeviciute et al, 2021). Sharma et al (2020), based on a comprehensive account of macro-botanical remains and direct dates of food grains from Binjor, an Indus Valley (Harappan) site in northwestern India, revealed that the area was occupied by an agricultural society during the Early Phase (ca. 2900−2600 BCE).…”
Section: Late Glacial Tomentioning
confidence: 69%
“…Sharma et al (2020), based on a comprehensive account of macro-botanical remains and direct dates of food grains from Binjor, an Indus Valley (Harappan) site in northwestern India, revealed that the area was occupied by an agricultural society during the Early Phase (ca. 2900−2600 BCE).…”
Section: Agricultural Practices and Other Human Activities: Global Co...mentioning
confidence: 99%
“…Several studies have been conducted along the palaeo-channel of Ghaggar (erstwhile Saraswati) river, originating from northwest Himalayas and supposed to have own southwest towards the Gujarat Kachchh region (Chatterjee et al, 2019;Ghose et al, 1979;Giosan et al, 2012;Gupta et al, 2004;Joshi et al, 1984;Kar et el., 2004;Lal, 2002;Marshall, 1931;Oldham, 1886Oldham, , 1893Possehl, 1999;Singh et al, 2017;Yashpal et al, 1980). This relict channel is thought to have catered several pre-historic phases of human civilizations of Indus culture in the north-western India (Giosan et al, 2012;Lal et al, 2003;Marshall, 1931;Mughal, 1997;Possehl, 2002, Sharma et al, 2020aVats, 1940 and references therein). The site 4MSR (locally known as Binjor) evolved from a typical agricultural settlement to a major rural industrial centre that manufactured copper artefacts, beads from semi-precious stones and a wide variety of terracotta products and may have exported them to other urban Harappan sites nearby and far-ung areas.…”
Section: Chronology Archaeological Background and Macro-botanical Det...mentioning
confidence: 99%
“…While palaeo-climatologists broadly in agreement about monsoonal dryness prevailing during the latter part of the mature phase (Dixit et al, 2014;Giosan et al, 2012;Gupta et al, 2003;Kathayat et al, 2017;Mac Donald, 2011;Sarkar et al, 2016;Staubwasser et al, 2003Wasson et al, 1984, archaeo-botanists continue to debate its impact(s) on agriculture Pokharia et al, 2011Pokharia et al, , 2014Pokharia et al, , 2017Sharma et al, 2020a;Singh et al, 1971Singh et al, , 1974. These studies yield two schools of thoughts: (i) monsoonal climate played a major role in shaping up the Harappan life-style, especially its subsistence (Bates et Pokharia et al 2011Pokharia et al , 2014Pokharia et al , 2017Sharma et al, 2020a;Sarkar et al, 2016;Weber 2003) and (ii) Harappan farming ironically arrived during deteriorating monsoonal conditions and was adaptive in nature, since its inception. Geological records largely support the latter view (Berkelhammer et al, 2012;Dixit et al, 2014;Enzel et al, 1999;Giosan et al, 2012Giosan et al, , 2018Gupta et al 2003; Kathayat et al, 2017;Mac Donald, 2011;Prasad and Enzel 2006;Staubwasser et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The palynological study involves the identification of pollen using a traditional transmitted light microscope (LM) to understand palaeovegetation, palaeoecology and palaeodiets of humans and domestic animals (Yao et al, 2012;Tang et al, 2014;Basumatary et al, 2020). Several members of the subfamily Papilionoideae are a good source of food grain since ancient times (Sharma et al, 2021). The pollen morphological characters of these are not very distinguishable under Light Microscope and are in general grouped either under subfamily or generic level which fails to provide any clue related to the climate-culture relationship.…”
Section: Introductionmentioning
confidence: 99%